Nifedipine for Acute Tocolysis of Preterm Labor: A Placebo-Controlled Randomized Trial. Issue 1 (July 2021) - Hawkins, J. Seth; Wells, C. Edward; Casey, Brian M.; McIntire, Donald D.; Leveno, Kenneth J.
Abstract : OBJECTIVE: To evaluate the effectiveness of acute nifedipine tocolysis in preventing preterm birth in women in preterm labor. METHOD: This was a randomized, double-blind, placebo-controlled trial of nifedipine in women with a singleton pregnancy between 28 0/7 and 33 6/7 weeks of gestation who were admitted with uterine activity, intact membranes, and cervical dilatation from 2 to 4 cm. Women were randomized to receive nifedipine 20 mg or placebo orally, followed by a repeat dose after 90 minutes if contractions persisted. The study drug was continued every 4 hours to complete a 48-hour regimen. The primary outcome was birth before 37 weeks of gestation. A total of 150 women were necessary to detect a one-third reduction in this outcome. After treating 88 patients, a preplanned interim analysis of blinded outcomes by the Data Safety Monitoring Committee recommended discontinuation of the trial due to futility. RESULTS: A total of 90 women were enrolled between May 2014 and November 2017. After two women withdrew, 88 were analyzed: 46 in the nifedipine group and 42 in the placebo group. There was no significant difference in the primary outcome of delivery before 37 weeks of gestation in the nifedipine group compared with the placebo group (52% vs 48%, relative risk [RR] 1.1, 95% CI 0.7–1.7), nor in the secondary outcome of delivery at least 48 hours from randomization (78% vs 71%, respectively, RR 1.1, 95% CI 0.9–1.4). There were also no significant differences between groups in neonatal outcomes. CONCLUSION: Acute tocolysis of preterm labor with nifedipine did not affect preterm birth rates, delivery within 48 hours, or neonatal outcomes. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT02132533. Abstract : Acute tocolysis of preterm labor with nifedipine did not reduce the frequency of preterm birth, with the interim analysis demonstrating futility for study continuation.